Tradição e relativismo moral em Alasdair Macintyre - Brugnera, Nedilso Lauro (2015)
Alasdair MacIntyre is a Scottish philosopher rooted in the USA. His projection began from the 1980s, after the publication of After Virtue. The first part of this title focuses on the criticism of the Enlightenment design, which is characterized by the search in giving morality a rational and universal justification, free of teleological influences and independent of traditions. MacIntyre aims to develop an ethic theory rescuing the classical concept of virtue, but adapting it to the contemporary way of life. To elaborate this unitary concept, he makes a study of the morality since the Homeric societies till the medieval world. The result of this study is a virtue concept that is articulated by a particular concept of practice, unity narrative of human life and the moral tradition. MacIntyre rejects a purely formal approach in relation to the morality. More specifically, he rejects the attempt to transcend the history, language and culture particularities to reach an impersonal perspective to make moral judgments. MacIntyre therefore argues that the only viable bases to the moral discourse are the social circumstances and practices of daily life. In this concept of unitary virtue, it becomes important his understanding about tradition. For him, tradition is not the antithesis of reason or something obsolete. On the contrary: it is a historically extended argument and socially incarnated, that shapes the identity of a person and of a nation. Beyond that, traditions are historical and dialectical movements which are formulated and reformulated as principles that serve as conceptual schemes, interpretation requirements that guide the action of their followers. Thus, traditions represent a conception of research that results in the elaboration of a mode of social and moral life, i.e., they provide a conception of rationality that MacIntyre denominates as narrative rationality. This rationality is constituted by the tradition and its constitutive: since we have learned to judge the truth and false through the resources of tradition in which we are formed, MacIntyre says the rationality is constituted by tradition; and since we use our rationality to involve ourselves in the world, and this involvement can bring discoveries that force us to change the rational resources of our traditions, the rationality is constitutive of the tradition. It’s through this rationality conception that MacIntyre evaluates to overcome both the objection and the relativistic perspectives which it is imputed by some of his critics.